Wag the dog - Rosenthal, Jane, 1956-; De Niro, Robert; Levinson, Barry; Henkin, Hilary; Mamet, David; Hoffman, Dustin, 1937-; Leary, Denis; Nelson, Willie, 1933-; Martin, Andrea, 1947-; Dunst, Kirsten, 1982-; Macy, William H., 1950-; Knopfler, Mark.; et al. ([Calif.] : New Line Home Video, 1998)
When the President is caught in a sex scandal less than 2 weeks before the election, "Mr. Fix-it" decides they need a war to distract the public's attention and he calls on Hollywood's top producer to create it.
Based on the book "American hero" by Larry Beinhart.
Videodisc released of the 1997 motion picture.
Special features: fullscreen version formatted to fit TV and widescreen version with original 1.85:1 original aspect ratio ; audio commentary by Barry Levinson and Dustin Hoffman ; featurette From Washington to Hollywood and back ; essay The line between truth and fiction : an essay on politics and the media ; theatrical trailer ; cast and crew biographies and filmographies.
New Line Home Video: N4658.
Director of photography, Robert Richardson ; editor, Stu Linder ; music, Mark Knopfler.
Dustin Hoffman, Robert De Niro, Denis Leary, Willie Nelson, Andrea Martin, Kirsten Dunst, William H. Macy.
Keywords: Presidents -- United States -- Election -- Drama; Political satire -- Drama; Feature films; Comedy films; Satirical films; Film adaptations; Video recordings for the hearing impaired